CD4 T-lymphocyte cell counts and pneumonia in HIV children - Siti Habsyah Masri (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2018)
CD4 T-lymphocyte cell counts and pneumonia in HIV-infected childrenAbstractBackground Pneumonia is a major cause of morbidity and the most common cause of mortality in infants and children who are infected with Human Immunodeficiency Virus (HIV). For HIV-infected children, the risk for developing pneumonia has been closely related to an individual’s having a lower CD4 T-lymphocyte cell count.Objective To evaluate for an association between CD4 T-lymphocyte cell count and pneumonia in HIV-infected childrenMethods. A cross sectional study was conducted among all children diagnosed with and without pneumonia who had HIV at Adam Malik Hospital, Medan. Data were taken from patients’ medical records between January 2008 to December 2015. We studied demographic, clinical, radiological and CD4 T-lymphocyte cell counts on admission, as well as mortality outcomes.Results  A total of 174 HIV-infected children were included in this study. Pneumonia was found in 47 children with 39 months as the median age of onset. The mean difference in CD4 levels was 0.912 cells/mm3 units (95% CI to -5.79 to 7.62) with higher mean in the pneumonia group than in the non-pneumonia group, but no significant difference. In addition, no significant association were found between nutritional status and incidence of pneumonia [OR 1,050; 95% CI 0,537 to 2,053); P = 0.886) or between immunodeficiency status and pneumonia, [OR 0.986;(95% CI 0,25 to 3.885);P= 0,984]. The common opportunistic infection in our subjects besides pneumonia were diarrhea, oral candidiasis and pulmonary TB, or some combination there of.  Severe malnutrition was also present in some subjects.Conclusions There is no significant association between CD4 T-lymphocyte cell count and pneumonia in HIV-infected children Key words CD4, HIV, pneumonia, children